Scanning Electron Microscope Comparative Evaluation of Feldspathic Porcelain Surfaces under Irradiation by Different Powers of Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) Laser - Hosseini, Mohammad Hashem; Sobouti, Farhad; Etemadi, Ardavan; Chiniforush, Nasim; Bouraima, Stephane Ayoub (Journal of Lasers in Medical Sciences, 2013)
Introduction: Recent use of lasers for porcelain surface treatment for adhesion of brackets to restorations has not only showed some promising results, but is also accompanied with less undesirable effects among other advantages. The purpose of this study is the comparative electron microscope evaluation of feldspathic porcelain surfaces under irradiation by Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) with different powers (0.75, 1.5 and 2W) via the acid etching with hydrofluoric acid (HF) technique. Methods: The glazed porcelain samples were obtained by duplicating labial surfaces of maxillary central incisor teeth. The specimens were randomly treated by 4 different methods. Group1 was etched with hydrofluoric acid 9.6%. Samples in group 2 to 4 were also irradiated by Nd:YAG laser with different powers: 0.75, 1.5 and 2W. Then the samples were prepared for evaluation by scanning electron microscope (SEM). Results: Etching quality from a porosity point of view was similar for group2 and HF group. Laser with power of 0.75W has little potential to create mechanical porosity. Conclusion: In regard of the results of this study, it is possible to benefit from Nd:YAG laser with appropriate parameters for surface conditioning.